MEASURING SECONDARY SCHOOL STUDENTS' CONTENT AWARENESS FOR DIGITAL TRANSFORMATION (Third Sector Social Economic Review, 2023)
Today, there is a rapid growth in the production and consumption of information and technology. The production, control and usage of technology are carried out by people with digital transformation awareness. In this study, it was aimed to reveal the digital transformation awareness of secondary school students. Quantitative research approach was used in the study. In the research, a questionnaire was applied between 14/12/2021-22/02/2022 by simple random sampling method to secondary education in Bilecik and data of 1196 students were obtained. Factor analysis and structural equation modeling were used in the statistical evaluation of the data. As a result of the analysis, the Digital Transformation Content Awareness Scale consisting of 3 factors and 41 items was obtained. The hypotheses about the students' district, gender, age, class, school type, program, field/branch, department, tablet/phone/computer use and duration, information source, being aware of activities and activities were tested. In addition, whether the content awareness of secondary school students differs according to demographic characteristics was determined as a sub-objective. As a result of the study, no statistically significant difference was found according to gender, age and students' tablet/phone/computer use; It has been determined that there was a significant difference according to the district, grade level, school type, program type, field / branch type, department, tablet / phone / computer usage time, information sources and being aware of activities and activities.
Keywords: Secondary Education; Digital Transformation; Industry 4.0; Scale Development; Factor Analysis